2013
DOI: 10.1007/s12035-013-8584-6
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Remyelination in Multiple Sclerosis: Friend or Foe?

Abstract: Myelination is critical to normal functioning of the vertebrate nervous system. In demyelinating diseases such as multiple sclerosis, oligodendrocytes, the myelinating cells in the central nervous system, are targeted, resulting in myelin loss, axonal damage, and severe functional impairment. While spontaneous remyelination has been proven a failure in multiple sclerosis, understanding the molecular mechanism underlying oligodendrocyte biology, myelination, and remyelination becomes crucial. To date, a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…The canonical Wnt pathway is activated when extracellular Wnt binds to Frizzled membrane receptors, resulting in the stabilization of intracellular β-catenin, which enters the nucleus to promote Wnt gene transcription (Xie et al, 2014). Shimizu et al (2005) showed that OPC differentiation in the spinal cord is inhibited by Wnt signaling through the canonical β-catenin pathway (Shimizu et al, 2005).…”
Section: Restoring Function: Mediators Of Oligodendrocyte Regeneramentioning
confidence: 99%
See 2 more Smart Citations
“…The canonical Wnt pathway is activated when extracellular Wnt binds to Frizzled membrane receptors, resulting in the stabilization of intracellular β-catenin, which enters the nucleus to promote Wnt gene transcription (Xie et al, 2014). Shimizu et al (2005) showed that OPC differentiation in the spinal cord is inhibited by Wnt signaling through the canonical β-catenin pathway (Shimizu et al, 2005).…”
Section: Restoring Function: Mediators Of Oligodendrocyte Regeneramentioning
confidence: 99%
“…Daam2 may be a potential upstream target of Wnt as its activation inhibits OPC differentiation in development and white matter injury (WMI) (Lee et al, 2015). Although there is a general consensus that canonical Wnt signaling inhibits OPC differentiation, conflicting findings have been reported (Xie et al, 2014). Wnt/β-catenin signaling pathway is essential for myelin protein expression and myelin sheath compaction in zebrafish (Tawk et al, 2011).…”
Section: Restoring Function: Mediators Of Oligodendrocyte Regeneramentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the capacity of ␤-catenin to modulate inflammatory and immune responses (71) could be related to its ability to modulate the expression of IFN-␤, which is a major regulator of immunity and inflammatory responses. Also, cross talk between ␤-catenin and IFN-␤ during the establishment and/or treatment of neurological disorders, such as Alzheimer's disease and multiple sclerosis, should be considered, since both the Wnt/␤-catenin pathway and the IFN-␤ response have been associated with these neurological pathologies (72)(73)(74). Although modulation of the constitutive level of IFN-␤ expression has probably been observed in the past by many researchers, it has often been neglected because it seemed to be only a minor response compared to pathogen-induced IFN-␤ expression.…”
Section: Licl Treatment Enhances Constitutive Ifn-␤ Gene Expressionmentioning
confidence: 99%
“…Wnt/β-catenin and Sonic HedgeHog (SHH) morphogen signallings both regulate embryonic neurogenesis and angiogenesis [123,124] and are variably associated with the remyelination process [125] and BBB integrity [126]. Nogo-A is an axonal growth inhibitor, and negative regulator of CNS angiogenesis [127]; anti-Nogo IgGs have been shown to suppress EAE through an immunomodulatory activity and the removal of remyelination obstacles between axons and new myelinating membranes [128].…”
Section: Other Angiogenic Molecules Potentially Involved In Ms and Eamentioning
confidence: 99%